Un patrimoine vivant - Alice Thomine-Berrada (In Situ)
This contribution explores the strong link between teaching and the anatomy collections, which has existed in the École des Beaux Arts since the late 18th century and can still be observed today. It related the history of the amphitheatre of anatomy, built by Félix Duban in 1845 to replace a building whose amphitheatre was too small, as it had been created, by François Debret, mainly to host Jean-Joseph Sue’s famous collection (in 1824). In 1869, Duban added a study gallery to it, located on the first floor and meant for the display of the anatomy collections, whose importance increased under the leadership of anatomy teachers from the second half of the 19th century, from Pierre-Charles Huguier to Paul Richer.